The influence of the directivity of the geometric structure on the load capacity of single-lap adhesive joints - Zielecki, Władysław; Bąk, Łukasz; Guźla, Ewelina (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
The aim of the work was to investigate the influence of the directivity of the geometric structure obtained in the grinding process on the load capacity of single-lap adhesive joints made of steel S235JR and aluminum alloy 2024-T3. The research was carried out for five different variants of joints differing in the direction of grinding and the arrangement of the ground surfaces to each other. The test results show that in the case of steel joints, the most advantageous solution in terms of joint load capacity is grinding the adhesive surfaces at an angle of 45˚ to the direction of the force loading the joint and connecting them in such a way that the created texture crosses (joint load capacity Pt = 4667.36 N). However, in the case of joints made of aluminum alloy, the best solution is to grind the adhesive surfaces perpendicular to the direction of the force loading the joint (joint load capacity Pt = 3210.46 N). The results of the significant difference test (test-t) show that in the assumed range of variability of the input parameters, the directionality of the geometric structure has a significant impact on the load capacity of the adhesive joints. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)